Clinical Profile of Haemophilia In Children in A Tertiary Care Hospital (Bangladesh Journal of Child Health, 2013)
Introduction : Haemophilias are the most common inherited coagulation disorders transmitted by X- linked recessive fashion affecting the males and females are the carriers of the disease. Haemophilias are distributed worldwide and have heterogeneous presentation depending upon its severity starting from neonatal period. Knowledge of spectrum of presentation of haemophilia helps in early diagnosis and planning of management. Objectives : To observe the clinical presentation of haemophilia in children Methodology : This observational study was carried out in the Department of Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University for a period of one year from 1st July 2007 to 30th June 2008. Clinical profile of 50 diagnosed cases of haemophilia